Assistance to Baitul Qur'an Santri in Recognizing Types of Waste and Their Processing: Pendampingan Santri Baitul Qur’an dalam Pengenalan Jenis Sampah Serta Pengolahannya - Sri Wahyuni; Martalasari, Martalasari; Dinata, Marta; Sari, Ermina; Awal, Raudhah (Universitas Lancang Kuning, 2024)
Baitul Qur'an Islamic Boarding School Campus 3 which is located in the West Rumbai District Area, including Pekanbaru City, this campus has a very extensive educational environment so it is necessary to carry out maintenance to maintain the cleanliness of the boarding school, especially for students who may not have knowledge about classifying types of waste and the processor. For this reason, the service team wants to provide education on the introduction of types of waste and their processing. This outreach activity was attended by students, especially at the Aliyah and MTs levels. In the pretest, the percentage of participants who understood various aspects of waste management ranged from 12% to 76%, with the lowest understanding in electronic waste management and the highest in the definition and types of waste. After the counseling was carried out, the results were that participants were very enthusiastic in this activity, so that in the posttest activity the results were 100% of the 25 participants understood the activities carried out.